Toward Effective Preventive Criminal Policy in Village Financial Governance: Evidence from the Village Guard Prosecutor Program in Simalungun District - Sanda Wiarhan Yahya Gultom; Faisal Riza (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Village financial management is a key component of village autonomy as regulated by Law Number 6 of 2014 concerning Villages. The significant increase in village fund allocations has not been matched by adequate human resource capacity, legal understanding, or effective oversight, increasing the risk of irregularities and corruption. Repressive criminal policies are considered ineffective as they are implemented only after financial losses occur, making preventive approaches more necessary. This study aims to analyze the effectiveness of a preventive criminal policy approach through the Village Guard Prosecutor Program in Simalungun District. It employs an empirical juridical method with a qualitative approach, using interviews, observations, and document analysis. The findings reveal that irregularities mainly arise from abuse of authority, weak supervision, and low legal awareness among village officials. The program applies preventive measures through legal counseling, administrative assistance, proactive supervision, and the use of technology, contributing to improved legal awareness, transparency, and accountability. However, challenges persist, including limited human resources, low legal and technological literacy, and weak inter-agency coordination. Overall, this approach demonstrates a promising direction toward more effective and accountable village financial governance.